Atmospheric‐pressure nonthermal plasma synthesis of ammonia over ruthenium catalysts. Issue 6 (28th October 2016) - Kim, Hyun‐Ha; Teramoto, Yoshiyuki; Ogata, Atsushi; Takagi, Hideyuki; Nanba, Tetsuya
Abstract : Atmospheric‐pressure nonthermal plasma was used to synthesize ammonia from nitrogen and hydrogen over ruthenium catalysts. Formation of NH3 in a N2 ‐H2 mixture altered the plasma characteristics due to the low ionization potential of NH3 (10.15 eV). The optimum gas ratio was found at N2 :H2  = 4:1 by volume (i.e., N2 ‐rich conditions). When plasma was operated at a temperature below 250 ° C, the NH3 concentration increased linearly with increasing specific input energy (SIE). For the Ru(2)‐Mg(5)/γ‐Al2 O3 catalyst at 250 ° C, pulse energization was four times more efficient than the AC energization case. The presence of RuO2 was found to be beneficial for the NH3 synthesis via plasma‐catalysis. The addition of a small amount of O2 was found to be effective for the in situ regeneration of the deactivated catalyst. The effect of metal promoters was in the order of Mg > K > Cs > no promoter. Abstract : Plasma‐catalysis was studied to synthesis ammonia (NH3 ) at atmospheric pressure and temperatures near light‐off of Ru‐based catalysts. We found that the interaction of plasma and catalyst become significant when plasma‐catalyst reactor is operated at light‐off temperature of catalyst. Energy yield of NH3 synthesis was reached up to 36 g‐NH3 /kWh in this study, while it was less than about 2 g‐NH3 /kWh.